Personality traits and examination anxiety: Moderating role of gender - Asghari, Arezou; Abdul.Kadir, Rusnani bte; Elias, Habibah bte; Baba, Maznah bte (Alberta Journal of Educational Research, 2013)
This study is aimed at examining the moderating effect of gender on the relationship between personality traits and state anxiety. The participants were 375 Iranian high school students (193 males and 182 females). The instruments used were the NEO-FFI-3 Inventory and State Anxiety Inventory. Results of the structural model showed that from the five personality dimensions, extraversion and conscientiousness negatively related to state anxiety whereas neuroticism affected it positively. Results of multigroup analysis also revealed that gender moderated the paths between extraversion and state anxiety in female students and conscientiousness and state anxiety in male students. Overall, findings suggested that both personality traits and gender differences can be determinant factors in state anxiety. Cette étude porte sur l’effet modérateur qu’a le sexe sur le rapport entre les traits de caractère et l’état d’anxiété. Les participants consistaient en 375 élèves iraniens au secondaire (193 hommes et 182 femmes). Le questionnaire NEO-FFI-3 et le questionnaire SAI sur l’anxiété (State Anxiety Inventory) ont servi d’outils à l’étude. Les résultats du modèle structurel ont indiqué que des cinq dimensions du caractère, l’extraversion et la conscience sont en relation négative avec l’anxiété, alors que le névrosisme est en relation positive. Les résultats d’une analyse multi-groupe ont également révélé que le sexe atténuait le rapport entre l’extraversion et l’anxiété chez les femmes, et entre la conscience et l’anxiété chez les hommes. Globalement, les résultats portent à conclure que tant les traits de caractère que les différences entre les sexes peuvent être des facteurs déterminants dans l’état d’anxiété.